Usia Perjanjian Lama - Nepho Gerson Laoly (STT Injili Indonesia Medan, 2019)
Why was the Old Testament established in the 1st century AD, long after its use for the Israelites. Then, if there are determined to be part of the Old Testament, then at least there are writings that do not meet the conditions. The existence of rejected writings is increasingly confirmed by the existence of the Song of Songs and the Ecclesiastes who at the last moment were